A Decenary Update on Metal Oxide Nanoparticles as a Heterogeneous Greener Catalyst for the Synthesis of Bioactive Heterocycles - Kamanna, Kantharaju; Badiger, Krishnappa B (Current Organocatalysis, 2023)
In recent years, heterocycle derivatives have emerged as promising molecules, and have exhibited remarkable pharmacological applications. The statistical data analysis of the presently available drug molecules in the market has revealed that more than 70% of the drug candidates are derived from the heterocycles. Various synthetic protocols have been established employing a wide range of catalysts and reaction conditions; among them, one of the catalytic areas includes nanomaterials of metals and metal oxides. Nanocatalysts play an important role in the organic transformation under green chemistry protocol, due to their recycling nature and provision of the required catalytic amount. In this review, we have provided a comprehensive summary of the recent progress made in the catalytic heterogeneous metal oxide NPs application, exclusively for the synthesis of heterocyclic compounds reported in the period from 2012 to 2021. Also, this review provides an inherent framework for the reader to select a suitable catalytic system of interest to synthesize desired oxygen, nitrogen, and sulphur heteroatoms containing heterocyclic scaffold with potential pharmacological activities.
Keywords: Nanocatalysts